THE MODEL OF LEGAL PROTECTION FOR PRODUCTS OF GENETIC ENGINEERING IN AGRICULTURAL TECHNOLOGY - Susanti, Dyah Ochtorina; Efendi, A’an; Sari, Nuzulia Kumala (Faculty of Law Universitas Trunojoyo Madura, 2019)
This research is aimed to find a new model of legal protection for the product of genetic engineering in the field of agricultural biotechnology. The concept of legal protection as coined by Philipus M. Hadjon is limited to administrative law in the relationship between the people and the government, not applicable to all fields of law. The legal protection for genetic engineering in the field of agricultural biotechnology is covered in laws and their derivative regulations as it evidently provides forum of compensation for the infringement of intellectual property resulted in genetic engineering in agricultural biotechnology. The contract becomes a special instrument of legal protection between owners of intellectual property in the field of agricultural biotechnology dealing with civil laws.